2022
DOI: 10.1371/journal.pone.0275523
|View full text |Cite
|
Sign up to set email alerts
|

The doubling effect of COVID-19 cases on key health indicators

Abstract: From the beginning of the COVID-19 pandemic, researchers advised policy makers to make informed decisions towards the adoption of mitigating interventions. Key easy-to-interpret metrics applied over time can measure the public health impact of epidemic outbreaks. We propose a novel method which quantifies the effect of hospitalizations or mortality when the number of COVID-19 cases doubles. Two analyses are used, a country-by-country analysis and a multi-country approach which considers all countries simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…An earlier study showed that increasing the number of tests helps to reduce the number of new COVID-19 cases [ 3 ]. Petrof et al [ 4 ] studied the effect of doubling of cases on key metrics, with the emphasis on hospitalizations and mortality. Demographic, social, health risk, medical and environmental factors influencing the risk of testing positive or negative were studied by Chaeau-Hyam et al [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study showed that increasing the number of tests helps to reduce the number of new COVID-19 cases [ 3 ]. Petrof et al [ 4 ] studied the effect of doubling of cases on key metrics, with the emphasis on hospitalizations and mortality. Demographic, social, health risk, medical and environmental factors influencing the risk of testing positive or negative were studied by Chaeau-Hyam et al [ 5 ].…”
Section: Introductionmentioning
confidence: 99%